Is metaphor a natural kind? - Garello, Stefana; Carapezza, Marco (Frontiers in Psychology, 2024)
In Metaphor Studies, metaphor is considered as a "form of understanding one thing in terms of something else". It is assumed that, despite their differences, metaphors share many properties and that a theory of metaphor should capture these essential properties. In short, it is assumed that metaphor is a natural kind. We call this view the Natural Kind Assumption. In this paper, we will challenge it and show that metaphor is not a natural kind. Finally, we will discuss the main philosophical consequences of this view.